2019
DOI: 10.12691/ajme-7-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of the Influence of Nozzle Temperature in FDM 3D Printed Pure PLA and Advanced PLA+

Abstract: This paper experimentally observed at a small level the influence of nozzle temperature change on warping deformation (WD), dimensional Accuracy (DA) and density. The materials chosen are pure PLA and advanced PLA+ specimens of rectangular shape of 63.5 mm × 9.53 mm × 3.2 mm produced by the end-user 3D printer based on fused deposition modeling (FDM). During the printing work, the nozzle temperature was conducted at twelve different values 195°C to 250°C with 5°C increments. Additionally, the infill density wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
(29 reference statements)
3
14
0
1
Order By: Relevance
“…Scanning electron microscopy (SEM) images presenting the cross-section of PLA samples printed at 200 and 230 °C confirm a significant reduction in the volume of voids (Figure S2). The subject of printing process optimization has been studied many times, but in the case of the present study, it is not the main purpose of the research; therefore the influence of printing parameters was not analyzed in detail. The initial low temperature of the nozzle caused a large number of voids in the structure, which translated into poor mechanical properties of the specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) images presenting the cross-section of PLA samples printed at 200 and 230 °C confirm a significant reduction in the volume of voids (Figure S2). The subject of printing process optimization has been studied many times, but in the case of the present study, it is not the main purpose of the research; therefore the influence of printing parameters was not analyzed in detail. The initial low temperature of the nozzle caused a large number of voids in the structure, which translated into poor mechanical properties of the specimens.…”
Section: Methodsmentioning
confidence: 99%
“…The traces were auto-leveled direction and set-up to a linear least-squares (LLS) fitting technique (single scan mode) and after that is filtered with a standard low-pass filter (LPF) of 0.8 mm effective cut-off wavelength. Full details of the measurement procedure have been reported elsewhere [18][19][20][21][22]. The calibration results using a standard ball of 22.0161 mm diameter (from Taylor Hobson Precision, Ltd.) after a series of trials showed that the system of the one-end cantilever beam was a linear massspring system regression of R 2 > 0.99, under various working and eco-friendly issues, with an absolute value of each uncertainty of <1% and displacement measurement resolution down to at worst performance of 50 nm.…”
Section: Surface Roughness Profile Inspectionmentioning
confidence: 99%
“…Main AM systems are fused deposition molding (FDM) [13], stereolithography (SL) [14], laminated object manufacturing (LOM) [15], selective laser sintering (SLS) [16] and laser engineered net shaping (LENS) [17]. One of the most widely used technologies for 3D printing compared to others competing for dimensional printing technologies is fused deposition modeling (FDM) [18,19,20,21,22] and it is this which is predicted as a sustainable modern manufacturing platform for functional and structural products and also for industrial and house-use [23].…”
Section: Introductionmentioning
confidence: 99%
“…This information set, taking into consideration the dimensional stability of POM (60–70%) compared to ABS (85–95%), allows the conclusion that 3D printing with this material will most likely result in warping without strong adhesive or high printing bed temperature. This deformation issue was raised by many investigators [ 17 , 18 , 19 , 20 ], with some prevention method outcomes including a properly adjusted extruder temperature and usage of a heated build plate [ 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%